Variations in Plant Water Use Efficiency Response to Manipulated Precipitation in a Temperate Grassland - Hai, Xuying; Li, Jianping; Li, Jiwei; Liu, Yulin; Dong, Lingbo; Wang, Xiaozhen; Lv, Wenwen; Hu, Zhenhong; Shangguan, Zhouping; Deng, Lei (Frontiers in plant science, 2022)
Water use efficiency (WUE) plays important role in understanding the interaction between carbon and water cycles in the plant-soil-atmosphere system. However, little is known regarding the impact of altered precipitation on plant WUE in arid and semi-arid regions. The study examined the effects of altered precipitation [i.e., ambient precipitation (100% of natural precipitation), decreased precipitation (DP, −50%) and increased precipitation (IP, +50%)] on the WUE of grass species ( Stipa grandis and Stipa bungeana ) and forb species ( Artemisia gmelinii ) in a temperate grassland. The results found that WUE was significantly affected by growth stages, precipitation and plant species. DP increased the WUE of S. grandis and S. bungeana generally, but IP decreased WUE especially in A. gmelinii . And the grasses had the higher WUE than forbs. For different growth stages, the WUE in the initial growth stage was lower than that in the middle and late growth stages. Soil temperature, available nutrients (i.e., NO 3 – , NH 4 + , and AP) and microorganisms under the altered precipitations were the main factors affecting plant WUE. These findings highlighted that the grasses have higher WUE than forbs, which can be given priority to vegetation restoration in arid and semi-arid areas.